PERITONEAL TUBERCULOSIS DIFFICULTIES OF THE DIFFERENTIAL DIAGNOSIS CASE REPORT - Mircea Onofriescu; Alexandru Luca; Anca Berescu; Alexandra Carp; Andrei Dumitrescu (European Scientific Journal, ESJ, 2014)
According to the US Centers for Disease Control and Prevention almost one third of the world’s population is infected with tuberculosis which kills almost 2 million people per year. Abdominal TB continues to be a significant health problem in the developing countries. Background: Female patients who present with ascites and adnexal tumors are presumed to have ovarian carcinoma. This can lead to radical surgery, hysterectomy with bilateral adnexectomy, with its associated morbidity. An important differential diagnosis to consider is peritoneal tuberculosis which can present in a similar manner and responds well to medical treatment only. Case presentation: A 44 year old Caucasian woman, presented to our gynecology clinic with abdominal distension, weight loss and asthenia, sent to us from gastroenterology were she first addressed for these symptoms. Ovarian malignancy was highly suspected so she was operated. The extemporaneous exam of the right ovary with the cystic mass, hysterectomy with bilateral adnexectomy, revealed caseating granulomas with epithelioid cells and Langhan’s type giant cells. Conclusion: There are few features that suggest the diagnosis of peritoneal TB rather than ovarian carcinoma. Apart from chest X-ray findings which may not always be present, also CT can help in the differential diagnosis. PCR and ADA testing of ascitic fluid can also be helpful. When these tests are or negative unavailable then diagnostic laparoscopy or laparotomy is needed, because with the help of frozen section we can avoid unnecessary radical surgery in cases of peritoneal tuberculosis that responds to medical treatment only.